Salmonella Enteritidis activates inflammatory storm via SPI-1 and SPI-2 to promote intracellular proliferation and bacterial virulence - Xiong, Dan; Song, Li; Chen, Yushan; Jiao, Xinan; Pan, Zhiming (Frontiers in Cellular and Infection Microbiology, 2023)
Salmonella Enteritidis is an important intracellular pathogen, which can cause gastroenteritis in humans and animals and threaten life and health. S. Enteritidis proliferates in host macrophages to establish systemic infection. In this study, we evaluated the effects of Salmonella pathogenicity island-1 (SPI-1) and SPI-2 to S. Enteritidis virulence in vitro and in vivo, as well as the host inflammatory pathways affected by SPI-1 and SPI-2. Our results show that S. Enteritidis SPI-1 and SPI-2 contributed to bacterial invasion and proliferation in RAW264.7 macrophages, and induced cytotoxicity and cellular apoptosis of these cells. S. Enteritidis infection induced multiple inflammatory responses, including mitogen-activated protein kinase (ERK-mediated) and Janus kinase-signal transducer and activator of transcript (STAT) (STAT2-mediated) pathways. Both SPI-1 and SPI-2 were necessary to induce robust inflammatory responses and ERK/STAT2 phosphorylation in macrophages. In a mouse infection model, both SPIs, especially SPI-2, resulted in significant production of inflammatory cytokines and various interferon-stimulated genes in the liver and spleen. Activation of the ERK- and STAT2-mediated cytokine storm was largely affected by SPI-2. S. Enteritidis ΔSPI-1-infected mice displayed moderate histopathological damage and drastically reduced bacterial loads in tissues, whereas only slight damage and no bacteria were observed in ΔSPI-2- and ΔSPI-1/SPI-2-infected mice. A survival assay showed that ΔSPI-1 mutant mice maintained a medium level of virulence, while SPI-2 plays a decisive role in bacterial virulence. Collectively, our findings indicate that both SPIs, especially SPI-2, profoundly contributed to S. Enteritidis intracellular localization and virulence by activating multiple inflammatory pathways.